Preparation of β-Myrcene-Chitosan Nanoparticles and Their Uptake and Toxicity in Aedes aegypti Larvae - Lara T. M. Costa; Bruna L. Rocha; Cleidiane C. Teixeira; Hemilly C. Martins; Mauren Cristine A. Silveira; Benedito Albuquerque; Alex Sander R. Cangussu; Peng He; Raimundo Wagner S. Aguiar; Ana Maria S. Maia; Guy Smagghe; Eugênio E. Oliveira (Insects)
Mosquito control still relies heavily on synthetic molecules, which can lead to the selection of resistant populations and undesirable environmental problems. This study described the preparation of a nanoparticle of the plant-derived molecule, β-myrcene, with chitosan, and the assessment of its toxicity against larvae of the yellow fever mosquito, Aedes aegypti. By producing fluorescent chitosan nanoparticles, we were able to observe their distribution in the digestive tract of larvae of Ae. aegypti. Chitosan-based nanoparticles containing β-myrcene (238 mg/L) could kill 100% of the larvae tested, whereas the blank control (i.e., the nanoparticle without β-myrcene) showed no larvicidal activity. The chitosan nanoparticles with β-myrcene had a zeta potential of +15 mV and a hydrodynamic diameter ranging from 30 to 2800 nm. The blank control, without β-myrcene, had a zeta potential of +26 mV and a diameter of 30 to 830 nm. Fluorescence analysis showed that the nanoparticles were efficiently absorbed and distributed in the digestive tract organs of the Ae. aegypti larvae. In short, our results reinforce the benefits of using chitosan to carry molecules of plant-derived-molecules, such as β-myrcene, in mosquito control, suggesting a broad internal distribution that contributes to their toxicity.